North Pacific dissolved inorganic carbon variations related to the Pacific Decadal Oscillation. Issue 3 (11th February 2014) - Yasunaka, Sayaka; Nojiri, Yukihiro; Nakaoka, Shin‐ichiro; Ono, Tsuneo; Mukai, Hitoshi; Usui, Norihisa
Abstract We elucidated multiyear variations of sea surface dissolved inorganic carbon (DIC) concentrations in the North Pacific from 2002 to 2008 by using monthly DIC maps derived from partial pressure CO2 observations. The Pacific Decadal Oscillation (PDO) was related to an east‐west seesaw pattern in the North Pacific DIC anomaly field. In the western North Pacific, DIC concentrations were relatively high from mid‐2002 to mid‐2005 and low after late 2007 compared with climatological values, and in the eastern North Pacific the opposite change was observed. Changes of the forcing factors associated with the PDO could explain the DIC east‐west seesaw pattern: horizontal advection, freshwater fluxes and vertical mixing in most regions, CO2 fluxes south of 40°N, and biological production in the subarctic.